The joy of signing : a dictionary of American signs - Riekehof, Lottie L. (Gospel Publishing House, 2014)
This is a guide for mastering the current basic signs used to communicate with deaf people in either the word order of the English language or in the American Sign Language pattern. It provides the basic vocabulary needed for persons entering interpreter training programs. Over 1500 signs have been illustrated and are grouped by chapter into their natural categories. Includes line drawings and step-by-step descriptions of positions and movements, information about the origins of signs, as well as the correct usage of signs in context.